Association between APOE Genotype and Change in Physical Function in a Population-Based Swedish Cohort of Older Individuals Followed Over Four Years - Skoog, Ingmar; Hörder, Helena; Frändin, Kerstin; Johansson, Lena; Östling, Svante; Blennow, Kaj; Zetterberg, Henrik; Zettergren, Anna (Frontiers in Aging Neuroscience, 2016)
The association between decline in physical function and age-related conditions, such as reduced cognitive performance and vascular disease, may be explained by genetic influence on shared biological pathways of importance for aging. The apolipoprotein E (APOE) gene is well-known for its association with Alzheimer’s disease (AD), but has also been related to other disorders of importance for aging. The aim of this study was to investigate possible associations between APOE allele status and physical function in a population-based longitudinal study of older individuals. In 2005, at the age of 75, 622 individuals underwent neuropsychiatric and physical examinations, including tests of physical function, and APOE-genotyping. Follow-up examinations were performed at age 79. A significantly larger decline in grip strength (p=0.015) between age 75 and 79 was found when comparing APOE ɛ4 allele carriers with non-carriers (10.3 (±10.8) kg versus 7.8 (±10.1) kg). No association was seen with decline in gait speed, chair-stand or balance. The association with grip strength remained after correction for cognitive and educational level, depression, cardiovascular disease, stroke, and BMI. This result supports the theory that APOE ɛ4 is an allele of importance for age-related phenotypes in general.